Deteksi Plagiarisme Source Code Tugas Mahasiswa Menggunakan Algoritma Cosine Similarity Dan Pembobotan TF-IDF - Eka Putra, I Gede Ariawan; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p67, 2022)
This research discusses the detection of plagiarism Source Code student assignments. The research purpose to design a system that can detect source code plagiarism on student assignments. The system designed using the Term Frequency weighting method — Inverse Document Frequency (TF-IDF) for word weighting and Cosine Similarity Algorithm to calculate the similarity between documents. By using this method, the test results obtained have similarities that are close to several documents from student assignment.